“Waitlist mortality” is high for myeloma patients with limited access to BCMA therapy - Ahmed, Nausheen; Wesson, William; Mushtaq, Muhammad Umair; Bansal, Rajat; AbdelHakim, Haitham; Bromert, Sarah; Appenfeller, Allison; Ghazal, Batool Abu; Singh, Anurag; Abhyankar, Sunil; Ganguly, Siddhartha; McGuirk, Joseph; et al. (Frontiers in Oncology, 2023)
• Manufacturing limitations led to limited access to ide-cel production slots in 2021.Amongst patients on the waitlist in 2021, 40% did not receive a production slot.• Median time from consultation for CAR-T to secure a production slot in 2021 was 1 month (range 0-23). Twenty percent of those who collected received a production slot beyond 6 months from the initial consultation.• Mortality is higher in RRMM patients who did not receive BCMA CAR-T, likely reflecting the effectiveness of BCMA CAR-T and stringent patient selection for limited CAR-T slots.